Early genetic screening and cardiac intervention in patients with cardiomyopathies in a multidisciplinary clinic - Chandu Sadasivan; Luke R. Gagnon; Deepan Hazra; Kaiming Wang; Erik Youngson; Jissy Thomas; Anita Y.M. Chan; D. Ian Paterson; Finlay A. McAlister; Tara Dzwiniel; Wayne Tymchak; Susan Christian; et al. (ESC Heart Failure)
Abstract Aims Patients with cardiomyopathies are a heterogeneous group of patients who experience high morbidity and mortality. Early cardiac assessment and intervention with access to genetic counselling in a multidisciplinary Cardiomyopathy Clinic may improve outcomes and prevent progression to advanced heart failure. Methods and results Our prospective cohort study was conducted at a multidisciplinary Cardiomyopathy Clinic with 421 patients enrolled (42.5% female, median age 58 years), including 224 patients with dilated cardiomyopathy (DCM, 42.9% female, median age 57 years), 72 with hypertrophic cardiomyopathy (HCM, 43.1% female, median age 60 years), 79 with infiltrative cardiomyopathy (65.8% female, median age 70 years) and 46 who were stage A/at risk for genetic cardiomyopathy (54.3% female, median age 36 years). Patients were seen in follow‐up at a median of 18 months. A pathogenic/likely pathogenic variant was identified in 28.5% of the total cohort, including 33.3% of the DCM cohort (28% TTN mutations) and 34.1% of the HCM cohort (60% MYBPC3 and 20% MYH7) who underwent genetic testing. The use of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers/angiotensin receptor neprilysin inhibitor (48.3–69.5% of total cohort, P < 0.001), β‐blockers (58.4–72.4%, P < 0.001), mineralocorticoid receptor antagonists (33.9–41.4%, P = 0.0014) and sodium/glucose cotransporter‐2 inhibitors (5.3–27.9%, P < 0.001) all increased at follow‐up. Precision‐based therapies were also implemented, including tafamidis for transthyretin amyloidosis (n = 21), enzyme replacement therapy for Fabry disease (n = 14) and mavacamten (n = 4) for HCM. Optimization of medications and devices resulted in improvements in left ventricular ejection fraction (LVEF) from 27% to 43% at follow‐up for DCM patients with reduced LVEF at baseline (P < 0.001) and reduction in left ventricular mass index (LVMI) from 156 g/m2 to 128 g/m2 at follow‐up for HCM patients with abnormal LVMI at baseline (P = 0.009). Optimization of therapies was associated with stable plasma biomarkers in stage B patients while lowering levels of BNP (619–517.5 pg/mL, P = 0.048), NT‐proBNP (777.5–356 ng/L, P < 0.001) and hsTropT (31–22 ng/L, P = 0.005) at follow‐up relative to baseline values for stage C patients. Despite stage B patients having overt cardiomyopathy at baseline, stage A and B patients had a similarly high probability of survival (χ2 = 0.204, P = 0.652). The overall cardiovascular mortality rate was low at 1.7% for the cohort (0.5% for stage B and 3.3% for stage C) over a median of 34‐month follow‐up. Conclusion Our study demonstrates that a multidisciplinary cardiomyopathy clinic can improve the clinical profiles of patients with diverse genetic cardiomyopathies.